EFEKTIVITAS PELAYANAN PEMUNGUTAN PAJAK BUMI DAN BANGUNAN DI DESA SUKALARANG KECAMATAN SUKALARANG KABUPATEN SUKABUMI - Ade Kuswanda; Andy Septiadi (Mimbar Administrasi Mandiri, 2025)
This study aims to analyze the effectiveness of land and building tax (PBB) collection in Sukalarang Village, Sukalarang Sub-district, Sukabumi District. The effectiveness of tax collection is analyzed based on three main aspects according to the theory of Zaidan Nawawi (2012), namely individual effectiveness, group effectiveness, and organizational effectiveness. This research used descriptive qualitative methods with data collection techniques through observation, interviews, and documentation. The research informants consisted of tax collection officers, village officials, and taxpayers who were selected using purposive sampling and snowball sampling techniques.The results showed that the effectiveness of PBB collection in Sukalarang Village still faces obstacles in various aspects. In the aspect of individual effectiveness, taxpayer awareness is still low, while tax officers' understanding of collection procedures still needs to be improved. In terms of group effectiveness, coordination between the village government and tax officials is not optimal, and socialization to the community is still limited. While in the aspect of organizational effectiveness, the PBB collection policy is quite good, but its implementation still needs to be improved through the use of technology and increasing the capacity of tax officers.The main factors affecting the effectiveness of PBB collection in Sukalarang Village include low taxpayer awareness, lack of socialization from the village government, limited tax collection personnel, and lack of technology utilization in the tax payment system. To improve the effectiveness of PBB collection, strategies are needed such as increasing education to the community, optimizing tax policies, utilizing online payment technology, and providing incentives for compliant taxpayers. With improvements in the tax collection system, it is expected that PBB revenue can increase, thus supporting sustainable development and community welfare.